1985
DOI: 10.1073/pnas.82.15.5010
|View full text |Cite
|
Sign up to set email alerts
|

Unusual apparently constitutive interferons and antagonists in human placental blood.

Abstract: We have detected seemingly uninduced interferons (IFNs) Chromatographic Products. Sephadex G-25 medium in pre-packed PD 10 columns, concanavalin A (Con A)-Sepharose and Blue Sepharose CL-6B (group-specific adsorbents), cyanogen bromide-activated Sepharose 4B, and activated CH-Sepharose 4B (coupling gels for antiserum immobilization), and acrylamide were purchased from Pharmacia. The standard proteins used for calibration of the slab gels were also from Pharmacia.Biological Preparations. Human placentas were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…The IFN produced by Sendai virus-induced trophoblasts seems to be distinct from that released from Sendai virus-infected human amniotic membrane (Duc-Goiran et al, 1983) and from that detected in human placental blood (Duc-Goiran et al, 1985). The latter two IFNs consist of ~ and B species as well as three other species neutralized to almost the same extent by IFN-~ and IFN-fl antibodies.…”
Section: Interferon Production By Cultured Human Trophoblasts and Chomentioning
confidence: 80%
“…The IFN produced by Sendai virus-induced trophoblasts seems to be distinct from that released from Sendai virus-infected human amniotic membrane (Duc-Goiran et al, 1983) and from that detected in human placental blood (Duc-Goiran et al, 1985). The latter two IFNs consist of ~ and B species as well as three other species neutralized to almost the same extent by IFN-~ and IFN-fl antibodies.…”
Section: Interferon Production By Cultured Human Trophoblasts and Chomentioning
confidence: 80%
“…The discovery that the bovine TP-1 promoter was active in JAR cells was surprising since these cells do not normally produce IFN unless induced by virus. IFN production by human placental tissues has been widely reported (1), and suggestions of a human placental-specific IFN have been made (47)(48)(49). Antiviral activity suggestive of IFN is associated with the conceptus and placenta in mice (50,51), hamsters (52), and pigs (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several workers (Chard et al, 1986;Duc-Goiran et al, 1985;Bocci et al, 1985) have reported the presence of IFN<t and -fl in amniotic fluids and specimens from placentae, however the cellular origins of these IFNs have not been identified. Besides IFN-~ and -fl, Chin et al (1986) have reported that IFN-~ is produced by placental lymphocytes, monocytes and granulocytes after phytohaemagglutinin and interleukin 2 stimulation.…”
Section: Introductionmentioning
confidence: 99%